2006
DOI: 10.1097/01.wnr.0000209043.66482.0b
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of tyrosine hydroxylase expression by sonic hedgehog

Abstract: Sonic hedgehog functions to induce £oor plate in early stages, and spinal motor neurons and midbrain dopaminergic neurons in later stages of development. Here, we investigated the e¡ects of sonic hedgehog on tyrosine hydroxylase expression in three cell lines that correspond to di¡erent stages of neural development. Sonic hedgehog increased the tyrosine hydroxylase gene expression in pluripotent P19 cells but repressed it in tyrosine hydroxylaseproducing PC12 cells. Promoter analysis in mouse neural stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Based on previous reports and our microarray results, we hypothesized that manipulation of these pathways at the appropriate developmental stage would affect dopaminergic neuronal differentiation process using our protocol. SHH is a member of the hedgehog family of signaling molecules, which are implicated in numerous developmental events, including growth and patterning of the neural tube [24][25][26][27][28]. SHH is a secreted signaling protein that binds to the receptor smoothened (SMO) and activates signal transduction pathway [24] that promotes differentiation of NSC or neural precursors into immature dopaminergic neurons [12,24,25].…”
Section: Functional Validations Of Microarray Resultsmentioning
confidence: 99%
“…Based on previous reports and our microarray results, we hypothesized that manipulation of these pathways at the appropriate developmental stage would affect dopaminergic neuronal differentiation process using our protocol. SHH is a member of the hedgehog family of signaling molecules, which are implicated in numerous developmental events, including growth and patterning of the neural tube [24][25][26][27][28]. SHH is a secreted signaling protein that binds to the receptor smoothened (SMO) and activates signal transduction pathway [24] that promotes differentiation of NSC or neural precursors into immature dopaminergic neurons [12,24,25].…”
Section: Functional Validations Of Microarray Resultsmentioning
confidence: 99%
“…Hedgehog (Hh) signaling is generally lower in adults than in embryos but was recently suggested to play an important role in the control of embryonic and adult stem cell growth [1]. Among the members of the mammalian hedgehog proteins (Sonic, Indian, Desert), sonic hedgehog (Shh) has received the most attention and acts on the target cells to increase the transcription of several genes, including members of Wnt , Notch , and several growth factors such as fibroblast growth factor, transforming growth factor β families, and the receptor Patched (Ptc), which releases the Ptc‐mediated repression of Smoothened (Smo) [2, 4]. It is known that the end point of the Shh signal pathway, representing the nuclear component of the pathway, is the zinc‐finger transcription factor Gli (Ci [Cubitus interruptus] in Drosophila species) [5].…”
Section: Introductionmentioning
confidence: 99%
“…As studies have shown that SHH antagonistically regulates cAMP dependent PKA in TH expressing cells (Kwon et al, ), we measured the cAMP levels in SHED and DPSCs at all 3 day points of induction. As represented in Figure , the cAMP levels in SHED (which express TH in their naïve state) was significantly reduced in the presence of the morphogen SHH on day 3 ( P < 0.05) and this reduced level persisted on days 6 and 9 ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have shown that higher expression of mature neuronal markers and dopaminergic markers did not preferentially predispose SHED for greater dopaminergic differentiation capacity than DPSCs. In fact, an earlier study showed that sonic hedgehog repressed TH expression in cells already expressing the marker spontaneously in naïve state (Kwon et al, ). The expression of the dopaminergic transcription factors En1, Nurr1, and Pitx3 in naïve SHED and DPSCs were found to be localized in the cytosol unlike in positive control cells, in turn suggesting their inability to functionally secrete dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation